Tap-based user authentication for smartwatches. Issue 78 (September 2018) - Nguyen, Toan; Memon, Nasir
Abstract: This paper presents TapMeIn, an eyes-free, two-factor authentication method for smartwatches. It allows users to tap a memorable melody ( tap-password ) of their choice anywhere on the touchscreen to unlock their watch. A user is verified based on the tap-password as well as her physiological and behavioral characteristics when tapping. Results from preliminary experiments with 41 participants show that TapMeIn could achieve an accuracy of 98.7% with a False Positive Rate of only 0.98%. In addition, TapMeIn retains its performance in different conditions such as sitting and walking. In terms of speed, TapMeIn has an average authentication time of 2 s. A user study with the System Usability Scale (SUS) tool suggests that TapMeIn has a high usability score.